Case Report of Aggressive Primary Pericardial Mesothelioma Presenting as a Constrictive Pericarditis. (March 2019) - Massicotte, Gabriel; Bernier, Mathieu; Piché, Marie-Eve; Cantin, Luce; Couture, Christian
Abstract : Supplemental Digital Content is available in the text.